H3S28 phosphorylation is a hallmark of the transcriptional response to cellular stress - Sawicka, Anna; Hartl, Dominik; Goiser, Malgorzata; Pusch, Oliver; Stocsits, Roman R.; Tamir, Ido M.; Mechtler, Karl; Seiser, Christian

(untitled) (Genome Research, 2014)
The selectivity of transcriptional responses to extracellular cues is reflected by the deposition of stimulus-specific chromatin marks. Although histone H3 phosphorylation is a target of numerous signaling pathways, its role in transcriptional regulation remains poorly understood. Here, for the first time, we report a genome-wide analysis of H3S28 phosphorylation in a mammalian system in the context of stress signaling. We found that this mark targets as many as 50% of all stress-induced genes, underlining its importance in signal-induced transcription. By combining ChIP-seq, RNA-seq, and mass spectrometry we identified the factors involved in the biological interpretation of this histone modification. We found that MSK1/2-mediated phosphorylation of H3S28 at stress-responsive promoters contributes to the dissociation of HDAC corepressor complexes and thereby to enhanced local histone acetylation and subsequent transcriptional activation of stress-induced genes. Our data reveal a novel function of the H3S28ph mark in the activation of mammalian genes in response to MAP kinase pathway activation.